2001
DOI: 10.1007/s003910170055
|View full text |Cite
|
Sign up to set email alerts
|

Zur Bedeutung des Gewichtsstatus für die Knochendichte bei Betagten und Hochbetagten

Abstract: Reduced bone density and osteoporosis are significant health problems and contributors to disability and mortality among older women and men. Therefore the decline of bone mineral content (BMC) and bone mineral density (BMD) are aspects of ageing with great medical and social significance. In recent years a low body weight was declared to be an important risk factor for the development of osteoporosis. In the present study the impact of weight status, defined by the categories of the WHO, on BMC of the whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…The correlations in all relationships were strong positive significant relationships (the right total hip, the left femoral neck, total left hip, lumbar 1 and 2 vertebrae, and total lumbar region in comparison to the right femoral neck which showed moderate positive relationship). Previous studies concluded that when BMI increases, BMD levels will also increase, which further supports our findings [37, 38]. Moreover, other studies explained that such relationship exists because heavy body weight could result in bone remodeling to compensate for the heavy mechanical load [39, 40].…”
Section: Discussionsupporting
confidence: 90%
“…The correlations in all relationships were strong positive significant relationships (the right total hip, the left femoral neck, total left hip, lumbar 1 and 2 vertebrae, and total lumbar region in comparison to the right femoral neck which showed moderate positive relationship). Previous studies concluded that when BMI increases, BMD levels will also increase, which further supports our findings [37, 38]. Moreover, other studies explained that such relationship exists because heavy body weight could result in bone remodeling to compensate for the heavy mechanical load [39, 40].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, correlations between BMI and BMD T-scores were significantly directly proportional although the correlation strength varied between the strong and moderate, which means that an increase in BMI could result in increased BMD T-scores, and vice versa. Previous studies concluded that when BMI increases, BMD levels will also increase, which further supports our findings [33][34]. Moreover, other studies explained that such a relationship exists because heavy body weight could result in bone remodeling to compensate for the heavy mechanical load [35][36].…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has found that as BMI rises, BMD rises as well. [29,30] According to some research, this association occurs because a high body weight can stimulate bone remodeling to compensate for the high mechanical strain. [31,32] Another study found that having a higher BMI raises the levels of leptin, which helps to maintain the connection by increasing osteoblast development and activity.…”
Section: Discussionmentioning
confidence: 99%